Manufacturing Sector Performance and Natural Resources Endowment: Evidence from Natural Resource-rich Sub-Saharan African Countries - Chile Nzeh Innocent; Benedict Ikemefuna Uzoechina; Millicent Adanne Eze; Chika Priscilla Imoagwu; Uzoma Miriam Anyachebelu (International Journal of Economics Development Research (IJEDR), 2021)
Theoretically, it has been observed that an abundance of natural resources that are not well harnessed can displace some vital sectors of the economy, especially the manufacturing sector. In this study, using annual series ranging from 1990-2019 and under the framework of a Panel ARDL, we investigated the link between natural resources endowment and the performance of the manufacturing sector in natural resource-rich SSA countries. Findings of our study show that in the short-run, natural resources endowment has an insignificant positive link with the manufacturing sector performance. However, in the long-run, the contribution of natural resources to the performance of the manufacturing sector becomes negative. On grounds of these findings, we recommend, among others; the diversification of the economies of this group into manufacturing sector by using proceeds from the export of natural resources to develop infrastructure necessary to improve the  sector.   Keywords : Natural resources, Manufacturing sector, Institutions, Panel ARDL, Employment, Inflation